Implementasi (EFA) Electronic File Archive Sederhana Berbasis Web - Suharmadi Suharmadi; Hendrik Setyo Utomo (Teknik Informatika, Politeknik Negeri Tanah Laut, 2019)
The process of filing the Company PT. PLN (Persero) Unit Induk Pembangkitan dan Penyaluran Kalimantan UPDK Barito ULPLTA Ir. P.M. Noor is storing files in the computers of each department. Communication between departments in archiving is done by means of whatapps or other tools, so that it requires a large file size. The purpose of the research is to design an electronic file archive (EFA) that applies to local networks that are connected to all departments. EFA is doing filing electronically and can communicate between users. Testing using the black box throughout the functional application is successful.